2017
DOI: 10.1007/s12032-017-0914-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress indicated by elevated expression of Nrf2 and 8-OHdG promotes hepatocellular carcinoma progression

Abstract: Reactive oxygen species (ROS) is excessively generated in tumors creating an oxidative stress in tumor microenvironment. We investigated hepatic expression of nuclear factor erythroid 2-related factor 2 (Nrf2) and 8-hydroxydeoxyguanosine (8-OHdG) in hepatocellular carcinoma (HCC) patients, and asked if ROS epigenetically upregulated Nrf2 and enhanced aggressiveness in HCC cells. Expression of Nrf2 (n = 100) and 8-OHdG (n = 53) was remarkably increased in HCC tissues compared with the noncancerous hepatic tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 32 publications
1
45
0
3
Order By: Relevance
“…Nrf2, as an antioxidative transcription factor responding to ROS, controls the antioxidant response element (ARE)‐dependent gene regulation under oxidative stress conditions (Lee & Johnson, ; Ma‐On et al, ). On activation, Nrf2 mediates the induction of a spectrum of cytoprotective proteins including phase II enzymes, such as NAD(P)H: quinone oxidoreductase (NQO1), and antioxidant proteins, such as HO‐1 and GSH, by ARE‐dependent pathway (He, Chen, Lin, & Ma, ; Itoh et al, ; Jia et al, ; Ma, Kinneer, Bi, Chan, & Kan, ; Nguyen, Sherratt, & Pickett, ).…”
Section: Discussionmentioning
confidence: 99%
“…Nrf2, as an antioxidative transcription factor responding to ROS, controls the antioxidant response element (ARE)‐dependent gene regulation under oxidative stress conditions (Lee & Johnson, ; Ma‐On et al, ). On activation, Nrf2 mediates the induction of a spectrum of cytoprotective proteins including phase II enzymes, such as NAD(P)H: quinone oxidoreductase (NQO1), and antioxidant proteins, such as HO‐1 and GSH, by ARE‐dependent pathway (He, Chen, Lin, & Ma, ; Itoh et al, ; Jia et al, ; Ma, Kinneer, Bi, Chan, & Kan, ; Nguyen, Sherratt, & Pickett, ).…”
Section: Discussionmentioning
confidence: 99%
“…OS is associated with the excessive generation of free radicals, such as reactive oxygen species (ROS), and/or decreased efficacy of antioxidant defenses. In humans, the pervasive impact of OS has been linked to the development of a variety of diseases as diverse as Alzheimer's disease [3], cancer [4], heart failure [5] and obesity [6]. OS is also a prevalent biomarker associated with the semen of approximately 35% of infertile men [7] and the presence of elevated levels of seminal ROS has been reported arising from male reproductive tract pathologies such as varicocele [8], inflammatory [9] and prostate cancer [10].…”
Section: Introductionmentioning
confidence: 99%
“…Previously, it was demonstrated that the Nrf2 pathway protects mice podocytes exposed to hyperglycemia partly through regulation of sirtuin 1 (Sirt1) activity (Q. ZHANG & al [29]). Another study reported that the expression of Nrf2 is enhanced by ROS formation and inhibited by antioxidants in hepatic cells (C. MA-ON& al [30]).…”
Section: Discussionmentioning
confidence: 99%